2021
DOI: 10.21203/rs.3.rs-505108/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Geographically Weighted Poisson Regression to Examine the Association Between Socioeconomic Factors and Hysterectomy Incidence in Wallonia, Belgium

Abstract: Background: Various studies have investigated geographical variations in the incidence of hysterectomy in Western countries and analyzed socioeconomic factors to explain those variations. However, few studies have used spatial analysis to characterize them. Geographically weighted Poisson regression (GWPR) explores the spatially varying impacts of covariates across a study area and focuses attention on local variations. Given the potential of GWPR to guide decision-making, this study aimed to describe the geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…However, a GWPR model is best for relaxing the fixed association assumption between the response and the explanatory variables thereby capturing spatial heterogeneity. Recent studies have shown that the applications of GWPR in a wide variety of fields, including but not limited to, analysis of the effects of demographic and socio-economic factors on the spatial variation of COVID-19 (Chen et al, 2022;Shawky et al, 2021;Zhang et al, 2021), health and other disease analysis (Bui et al, 2018 ;Chen et al, 2010;Goovaerts, 2005;Nakaya et al, 2005;Poliart et al, 2021;Yang et al, 2009), traffic crash modelling (Li et al, 2013;Zhao et al, 2004), population density and housing (Mennis and Jordan, 2005;Chen et al, 2017), poverty mapping (Benson et al, 2005;Loubert et al, 2018) and diseases mapping (Nakaya et al, 2005). In most of these studies, however, one of the challenges is the presentation and synthesis of the large number of "mappable" results generated by local GWR models.…”
Section: Statistical Methods To Derive Space-time Modelsmentioning
confidence: 99%
“…However, a GWPR model is best for relaxing the fixed association assumption between the response and the explanatory variables thereby capturing spatial heterogeneity. Recent studies have shown that the applications of GWPR in a wide variety of fields, including but not limited to, analysis of the effects of demographic and socio-economic factors on the spatial variation of COVID-19 (Chen et al, 2022;Shawky et al, 2021;Zhang et al, 2021), health and other disease analysis (Bui et al, 2018 ;Chen et al, 2010;Goovaerts, 2005;Nakaya et al, 2005;Poliart et al, 2021;Yang et al, 2009), traffic crash modelling (Li et al, 2013;Zhao et al, 2004), population density and housing (Mennis and Jordan, 2005;Chen et al, 2017), poverty mapping (Benson et al, 2005;Loubert et al, 2018) and diseases mapping (Nakaya et al, 2005). In most of these studies, however, one of the challenges is the presentation and synthesis of the large number of "mappable" results generated by local GWR models.…”
Section: Statistical Methods To Derive Space-time Modelsmentioning
confidence: 99%